Advanced Solar Photocatalytic Asphalt for Removal of Vehicular NOx. (December 2017) - Fan, Wenguang; Chan, Ka Yan; Zhang, Chengxu; Leung, Michael K.H.
Abstract: Conventional use of solar energy is to convert it into a useful form, e.g. heat or electricity. Alternatively, solar radiation can be used to activate photocatalyst for direct functional photocatalytic applications. In the present research, solar photocatalytic asphalt was developed for removal of vehicular nitrogen oxides (NOx ) to mitigate the roadside air pollution problem. Visible-light activated photocatalytic asphalt was fabricated by embedding carbon-modified titanium dioxide (C-TiO2 ) onto asphalt surface under proper heat treatment. Material characterizations were conducted to study the surface and light absorption properties. Chamber tests of NOx removal were conducted under the conditions that simulated the ambient environment under solar irradiation. The experimental results show that NOx removal by C-TiO2 photocatalytic asphalt is viable, and is better than the more commonly used P25. The parametric analysis also reveals that the material fabrication process can be optimized for making photocatalytic asphalt that is highly effective, durable and cost-effective. This study demonstrates successful use of solar radiation via photocatalysis for functional application that can solve environmental problem.